Human-Wildlife Conflict : Complexity in the Marine Environment - Edited by Draheim, Megan M. et.al (Oxford Oxford University Press, 2015)
Human-wildlife conflict (H.W.C) has classically been defined as a situation where wildlife impacts humans negatively (physically, economically, or psychologically), and where humans likewise negatively impact wildlife. However, there is growing consensus that the conflict between people about wildlife is as important as the conflict between people and wildlife. H.W.C not only affects the conservation of one species in a particular geographic area, but also impacts the willingness of an individual, a community, and wider society to support conservation programs in general. This book explores the complexity inherent in these situations, covering the theory, principles, and practical applications of HWC work, making it accessible and usable for conservation practitioners, as well as of interest to researchers more concerned with a theoretical approach to the subject. Through a series of case studies, the book's authors and editors tackle a wide variety of subjects relating to conflict, from the challenges of wicked problems and common pool resources, to the roles that storytelling and religion can play in conflict.
Include Illustrations, Tables and Index
Keywords: Wildlife management -- Wildlife conservation -- Marine resources conservation